Usability Factors as Antecedent and Consequence on Business Strategy and SERVQUAL: Nielsen & Mack Approach - Tasrik Hasrat; Khairina Rosyadah (Manunggal Halim Jaya, 2021)
The usability elements above can be used to support tourism business development, which is following the usability elements in the basic concept of User Experience. The use of qualitative methods is used to provide a detailed and detailed formulation of the value of each component in usability. In the end, the application of this study at the same time offers a study formulation on the user experience of the OYO application in Indonesia through the usability approach by Mack & Nielsen, (1995). Researchers determine the respondent by distributing questionnaires, the total population of consumers who use the OYO application. By using slovin formula as the respondent determinant, we obtained a full sample of 120 respondent. The results of this study state all hypothesis include direct and indirect effect have a positive and significant effect on dependent variables (business strategy and SERVQUAL). Usability is how certain users can use a product to achieve specific goals effectively, efficiently, and satisfy users. In general terms, usability is an attribute of quality used to evaluate how easy an interface is to use. User Experience is the perception and response of the user as a reaction to the use of a product, system, or service.